Outcome of endoscopic clearance of bile duct stones after endoscopic sphincterotomy (ES): Hospital Kota Bharu (HKB) experience - Ng Sze, How (2008)
Choledocholithiasis or common bile duct (CBD) stones are still frequently encountered in cholecystectomy patients. The use of endoscopic retrograde cholangiopancreaticography (ERCP) and endoscopic sphincterotomy (ES) in the management of CBD stones has progressed tremendously. However, the controversy is still present in Malaysia as its morbidity and morbidity can be significant. The present study is designed to assess the results of endoscopic clearance of CBD stones after ES in relation to the number, location and size of the stone with help of mechanical or electrohyraulic lithotripsy, Dormia basket and balloon catheter. It is also to evaluate its complications. Retrospective case review of 111 patients with CBD stones who had undergone ERCP from January 2003 to December 2005 in Hospital Kota Bharu (HKB), Kelantan. Data of those patients who fulfilled the criteria were documented and the clearance rate as well as the complications of the procedure were analysed using SPSS software (version 11.0). ERCP with ES was attempted in 111 patients and stone clearance was successful in 68 (61.3%) patients. 71 (64%) were female and 40 (36%) were male. The median age of male was 54 years old and of female was 49 years old. Female patients predominantly presented with smaller ( <1 0 mm), distally located and multiple stone. There were 51 (63.8%), 40 (64.5%) and 50 (66.7%) female patients with smaller, distally located and multiple CBD stones respectively. CBD stones which were <1 0 mm and distally located had more successful clearance while the number of stone showed no statistical difference. Complications occurred in 14 (12.6%) patients, bleeding in 4 (3.6%) patients, acute pancreatitis in 8 (7.5%) patients, sepsis or cholangitis as well as perforation each in I (0.9%) patient and no death was reported. Lastly, 7 (6.3%) patients needed surgical interventions and 2 of them had undergone emergency laparotomy for the complication and 5 patients required CBD exploration after failure to retrieve the stone byERCP. CONCLUSIONS: This study suggested that ERCP with ES continue to play an important and effective role in the management of CBD stones. Stone extraction by ERCP and ES has been found to be effective, safe and easy to perform. More importantly, it also has demonstrated that the smaller (<IOmm) and distally located stones were easier to retrieve regardless of the number of stones in the CBD. Moreover, an acceptable complication rate for endoscopic therapy of CBD stone in HKB was found comparable to elsewhere in the world. However, more stringent criteria with larger number of cases, review, and ongoing practice are needed to ensure optimal benefit to patients in the future.